2022
DOI: 10.3390/en15031094
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of the Effects of Biodiesel Fraction Increase on the Combustion Stability and Characteristics of a Reactivity-Controlled Compression Ignition Diesel-Biodiesel/Natural Gas Engine

Abstract: A single-cylinder marine diesel engine was modified to be operated in reactivity controlled compression ignition (RCCI) combustion mode. The engine fueling system was upgraded to a common rail fuel injection system. Natural gas (NG) was used as port fuel injection, and a diesel/sunflower methyl ester biodiesel mixture was used for direct fuel injection. The fraction of biodiesel in the direct fuel injection was changed from 0% (B0; 0% biodiesel and 100% diesel) to 5% (B5) and 20% (B20) while keeping the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The combustion duration is expressed as the value of CA passing between CA10 and CA90 [43]. Equation 12shows the model used to estimate the combustion duration based on different input parameters.…”
Section: Combustion Duration (Ca)mentioning
confidence: 99%
“…The combustion duration is expressed as the value of CA passing between CA10 and CA90 [43]. Equation 12shows the model used to estimate the combustion duration based on different input parameters.…”
Section: Combustion Duration (Ca)mentioning
confidence: 99%
“…Therefore, under heavier loads, engines running on biodiesel tend to experience a slower increase in pressure rate and consequently, the peak pressure is also lower compared to when using diesel fuel (Tamilselvan et al, 2017). Figure 3 shows the difference between cylinder gas pressure and heat release rate with the crank angle of diesel fuel and different biodiesels (Ramalingam and Mahalakshmi, 2020;Seraç et al, 2020;Silitonga et al, 2017;Zarrinkolah and Hosseini, 2022). The difference is not too large to require serious modifications to the engine, however, to avoid affecting the power experience that people are used to with diesel engines, many measures are still proposed by researchers which will be clarified in the next section.…”
Section: Effects Of Biodiesel On Combustion Characteristicsmentioning
confidence: 99%
“…Fig.3. The different between cylinder gas pressure and heat release rate with the crank angle of diesel fuel and different biodiesels(Ramalingam and Mahalakshmi, 2020;Seraç et al, 2020;Silitonga et al, 2017;Zarrinkolah and Hosseini, 2022)(a) soybean-based biodiesel (b) Moringa oleifera biodiesel (c) Jatropha curcas biodiesel (d) sunflower methyl ester biodiesel…”
mentioning
confidence: 99%
“…While the transportation sector is moving toward electrification to decarbonize its lightduty fleets, diesel technologies are still needed for mid-to heavy-duty and off-road applications. Interests in biodiesel have recently expanded into locomotives and ships [8][9][10]. Since Energies 2023, 16, 5010 2 of 10 biodiesel is much more carbon neutral than petrol diesel [11], its use is expected to increase in the near future due to the transition to a carbon-neutral economy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been multiple reports on air pollutant emissions using biodiesel blends over the years, with the majority of studies reporting less carbon monoxide, less particulate matter, and higher NOx emissions comparing with petroleum diesel [12][13][14][15]. Only a few studies have reported opposite trends in emissions [10]. People have come to realize that emissions are dependent on many factors, such as engine and feedstock specific conditions, engine operations, sample collection methods, etc.…”
Section: Introductionmentioning
confidence: 99%